A randomised controlled trial to assess the cost-effectiveness of intensive versus no scheduled follow-up in patients who have undergone resection for colorectal cancer with curative intent - David Mant; Alastair Gray; Siân Pugh; Helen Campbell; Stephen George; Alice Fuller; Bethany Shinkins; Andrea Corkhill; Jane Mellor; Elizabeth Dixon; Louisa Little; Rafael Perera-Salazar; et al. (Health Technology Assessment, 2017)
Background: Intensive follow-up after surgery for colorectal cancer is common practice but lacks a firm evidence base. Objective: To assess whether or not augmenting symptomatic follow-up in primary care with two intensive methods of follow-up [monitoring of blood carcinoembryonic antigen (CEA) levels and scheduled imaging] is effective and cost-effective in detecting the recurrence of colorectal cancer treatable surgically with curative intent. Design: Randomised controlled open-label trial. Participants were randomly assigned to one of four groups: (1) minimum follow-up (n = 301), (2) CEA testing only (n = 300), (3) computerised tomography (CT) only (n = 299) or (4) CEA testing and CT (n = 302). Blood CEA was measured every 3 months for 2 years and then every 6 months for 3 years; CT scans of the chest, abdomen and pelvis were performed every 6 months for 2 years and then annually for 3 years. Those in the minimum and CEA testing-only arms had a single CT scan at 12–18 months. The groups were minimised on adjuvant chemotherapy, gender and age group (three strata). Setting: Thirty-nine NHS hospitals in England with access to high-volume services offering surgical treatment of metastatic recurrence. Participants: A total of 1202 participants who had undergone curative treatment for Dukes’ stage A to C colorectal cancer with no residual disease. Adjuvant treatment was completed if indicated. There was no evidence of metastatic disease on axial imaging and the post-operative blood CEA level was ≤ 10 µg/l. Main outcome measures: Primary outcome Surgical treatment of recurrence with curative intent. Secondary outcomes Time to detection of recurrence, survival after treatment of recurrence, overall survival and quality-adjusted life-years (QALYs) gained. Results: Detection of recurrence During 5 years of scheduled follow-up, cancer recurrence was detected in 203 (16.9%) participants. The proportion of participants with recurrence surgically treated with curative intent was 6.3% (76/1202), with little difference according to Dukes’ staging (stage A, 5.1%; stage B, 7.4%; stage C, 5.6%; p = 0.56). The proportion was two to three times higher in each of the three more intensive arms (7.5% overall) than in the minimum follow-up arm (2.7%) (difference 4.8%; p = 0.003). Surgical treatment of recurrence with curative intent was 2.7% (8/301) in the minimum follow-up group, 6.3% (19/300) in the CEA testing group, 9.4% (28/299) in the CT group and 7.0% (21/302) in the CEA testing and CT group. Surgical treatment of recurrence with curative intent was two to three times higher in each of the three more intensive follow-up groups than in the minimum follow-up group; adjusted odds ratios (ORs) compared with minimum follow-up were as follows: CEA testing group, OR 2.40, 95% confidence interval (CI) 1.02 to 5.65; CT group, OR 3.69, 95% CI 1.63 to 8.38; and CEA testing and CT group, OR 2.78, 95% CI 1.19 to 6.49. Survival A Kaplan–Meier survival analysis confirmed no significant difference between arms (log-rank p = 0.45). The baseline-adjusted Cox proportional hazards ratio comparing the minimum and intensive arms was 0.87 (95% CI 0.67 to 1.15). These CIs suggest a maximum survival benefit from intensive follow-up of 3.8%. Cost-effectiveness The incremental cost per patient treated surgically with curative intent compared with minimum follow-up was £40,131 with CEA testing, £43,392 with CT and £85,151 with CEA testing and CT. The lack of differential impact on survival resulted in little difference in QALYs saved between arms. The additional cost per QALY gained of moving from minimum follow-up to CEA testing was £25,951 and for CT was £246,107. When compared with minimum follow-up, combined CEA testing and CT was more costly and generated fewer QALYs, resulting in a negative incremental cost-effectiveness ratio (–£208,347) and a dominated policy. Limitations: Although this is the largest trial undertaken at the time of writing, it has insufficient power to assess whether or not the improvement in detecting treatable recurrence achieved by intensive follow-up leads to a reduction in overall mortality. Conclusions: Rigorous staging to detect residual disease is important before embarking on follow-up. The benefit of intensive follow-up in detecting surgically treatable recurrence is independent of stage. The survival benefit from intensive follow-up is unlikely to exceed 4% in absolute terms and harm cannot be absolutely excluded. A longer time horizon is required to ascertain whether or not intensive follow-up is an efficient use of scarce health-care resources. Translational analyses are under way, utilising tumour tissue collected from Follow-up After Colorectal Surgery trial participants, with the aim of identifying potentially prognostic biomarkers that may guide follow-up in the future. Trial registration: Current Controlled Trials ISRCTN41458548. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 21, No. 32. See the NIHR Journals Library website for further project information.